2023
DOI: 10.7759/cureus.36584
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen Alleles Compatibility and Immunophenotypic Profile Associations in Infertile Couples

Abstract: Introduction: The maternal immune system has a major role in the successful embryo implantation and maintenance of the pregnancy. This study aimed to investigate the maternal immunophenotyping profile (percentage of Natural Killer [NK] cells and the CD4/CD8 [cluster designation] ratio in peripheral blood lymphocytes) and the HLA (Human Leukocyte Antigen)-DQA1 alleles sharing in infertile couples. Methods: This cross-sectional study included 78 women who had experienced at least two spontaneous misca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, this topic has not been followed up for decades. Recently, the presence of the HLA-DQA1*5 has been strongly associated with overall HLA-DQA1 compatibility in humans and has shown potential as a surrogate marker for assessing overall immunological compatibility in infertile couples [ 78 ]. In this study, we also identified H2-Aa, the homologous gene of HLA-DQA1, as one of the hub genes in antigen processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, this topic has not been followed up for decades. Recently, the presence of the HLA-DQA1*5 has been strongly associated with overall HLA-DQA1 compatibility in humans and has shown potential as a surrogate marker for assessing overall immunological compatibility in infertile couples [ 78 ]. In this study, we also identified H2-Aa, the homologous gene of HLA-DQA1, as one of the hub genes in antigen processing.…”
Section: Discussionmentioning
confidence: 99%